Statistical Significance versus Clinical Relevance: Key Considerations in Interpretation Medical Research Data - Yousif AbdulRaheem (Wolters Kluwer Medknow Publications, 2024)
Medical research plays a crucial role in advancing our understanding of various aspects related to health, including disease, risk factors, and patient management. However, the interpretation of research data becomes intricate when considering the notions of statistical significance and clinical relevance. It is not uncommon to interpret findings that demonstrate statistical significance as indicative of clinical relevance. To explain it in a more straightforward way, statistical significance, ascertained through statistical tests using the P value, indicates that an observed difference or association is improbable to occur by chance alone. Conversely, clinical relevance focuses on the practical implications of a finding in real-world contexts and determines whether an observed difference or relationship holds practical meaning. Recently, there have been issues and debates surrounding the idea of statistical significance as certain experts argue that its mathematical representation can be misleading when it comes to practical understanding. These experts propose the inclusion of additional measures like effect sizes and confidence intervals. A sound comprehension of both statistical and clinical dimensions is vital in order to ensure precise interpretation of data and facilitate well-informed decision-making in the practice of medicine. By doing so, it positively influences the health of individuals and communities.